Minor fishery for the Indian oil sardine (Sardinella longiceps) along Saurashtra coast - Gopal, C; Savaria, Y D (Indian Journal of Fisheries, 2011)
Major landings of oil sardine in India arefiom the southwestcoast(Anthony Raja 1969,Anonymous \9M). FotedarandSavaria(1988)reported oil sardine landings along the SaurashtraCbast during November 1986 - February1987. The present study was conducted toknow whether the oil sardine occurs regularlyalong the Saurashtra coast